6-methylmercaptopurine riboside, a thiopurine nucleoside with antiviral activity against canine distemper virus in vitro - Carvalho, Otavio Valerio de; Felix, Daniele Mendes; Tozato, Claudia de Camargo [UNESP]; Rangel Fietto, Juliana Lopes; Almeida, Marcia Rogeria de; Bressan, Gustavo Costa; Pena, Lindomar Jose; Silva-Junior, Abelardo (Biomed Central Ltd, 2017)
Background: Canine distemper (CD) is a widespread infectious disease that can severely impact a variety of species in the order Carnivora, as well as non-carnivore species such as non-human primates. Despite large-scale vaccination campaigns, several fatal outbreaks have been reported in wild and domestic carnivore populations. This, in association with expansion of the disease host range and the development of vaccine-escape strains, has contributed to an increased demand for therapeutic strategies synergizing with vaccine programs for effectively controlling canine distemper. 6-methylmercaptopurine riboside (6MMPr) is a modified thiopurine nucleoside with known antiviral properties against certain RNA viruses. Methods: We tested the inhibitory effects of 6MMPr against a wild-type CDV strain infection in cell culture. We measured infectious particle production and viral RNA levels in treated and untreated CDV-infected cells. Ribavirin (RIB) was used as a positive control. Results: Here, we report for the first time the antiviral effects of 6MMPr against canine distemper virus (CDV) in vitro. 6MMPr was able to reduce viral RNA levels and to inhibit the production of infectious CDV particles. The therapeutic selectivity of 6MMPr was approximately six times higher than that of ribavirin. Conclusion: Our results indicate that 6MMPr has high anti-CDV potential and warrants further testing against other paramyxoviruses, as well as clinical testing of the compound against CDV.
Keywords: Canine distemper; Antiviral; Azathioprine; Thiopurine; Nucleoside analogue